Problems Faced by Physical Education Teachers in the Online Learning Process During the Covid-19 Pandemic at MAN 2 Bengkulu City - Wahyudi Wahyudi; Supriyanto Supriyanto; Juwita Juwita (Sinar Sport Journal, 2021)
The purpose of this study was to find out the problems faced by physical education teachers in online learning during the COVID-19 pandemic at MAN 2 Bengkulu City. The location of this research was conducted at the school of MAN 2 Bengkulu City. This research is included in descriptive quantitative research and the population in this study are all physical education teachers at MAN 2 School Bengkulu City totaling 4 people. The results showed that the problems faced by physical education teachers in the online learning process (on the network) during the Covid-19 pandemic at MAN 2 Bengkulu City were in the hampered category. This is obtained from each category, such as in learning planning in this case the preparation of learning plans by the teacher by 75% stating it is hampering, the implementation of learning from home is known that 75% states it is inhibiting, and the assessment of learning from home is known that 50% states hinder.